THE HYDROCARBON BEARING CAPACITY OF MIOCENE RESERVOIR UNITS IN THE LIGHT OF BOREHOLE SEISMIC DATA - Ahmadov, Tofig R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The presented paper includes several results of seismic exploration that was conducted on the Zikh-Hovsan oilfields with the target areas of Miocene reservoirs that underlie the primary Productive Suite of Azerbaijan, Lower Pliocene reservoirs. In 2010, the VSP and offset VSP were conducted on these fields. The paper includes the first wave arrival times for the vertical depth-time relationship, as well as, the different types of waves (P, S, incident, reflecting and exchange), based on the VSP data analysis of three components (XYZ). In addition, the velocity calculated from the VSP data is presented, which correlates with sonic log data. Moreover, the VSP velocity analysis was carried out and the overpressured areas were identified. Furthermore, the results of overpressure analysis which are presented in this paper indicate the velocity of about 2000 m/s at the depths of more than 3900 m, which are supported by the seismic inversion. Stratigraphically, overpressure encompasses the Miocene stratigraphical units. In 2015 the well was drilled that confirmed the fact of oil presence and produced in about 100 tons of oil/day. This fact has also supported the hydrocarbon bearing capacity of Miocene stratigraphical units across Absheron peninsula and its continuation into the Caspian Sea.
Keywords: Miocene reservoirs; vertical seismic profiling; pneumatic source; frequency spectrum; sonic logging; seismic inversion; overpressure